Próba ewaluacji „dziennika” jako narzędzia badawczego - Derenowski, Marek (Neofilolog, 2019)
This article focuses on the use of teacher journals as an empirical tool. Journals are often perceived as subjective and self-indulgent, resulting from lack of criticism or lack of experience in journal writing. On the other hand, journals can help in investigating such aspects as learner behavior, classroom dynamics or teacher behaviors. Undoubtedly journals help teachers to become more reflective. However, the obvious advantages, the journals are not the most favored empirical research tool.